Effects of Different Levels of Dietary Crude Protein on Growth and Reproductive Performance of Broiler Breeder Birds - Talukdar, D.; Behura, N. C.; Sethy, K.; Mishra, P. C.; Nayak, G. D.; Mishra, S. K.; Behera, K.; Mishra, C. (International Journal of Bio-resource and Stress Management, 2023)
This study was conducted to evaluate the growth and reproductive quality of of male broiler breeder strain reared with diets having 8, 10, 12 and 14% CP. One hundred twenty male breeder chicks of color-synthetic male-line (CSML) strain were raised on common starter diet (20% CP, 2750 ME kcal kg-1 up to 5 weeks). On completion of 5 weeks, the birds were distributed in four treatment groups; each treatment groups comprised of 3 replicate groups and each replicate had 10 birds. The birds were restricted fed during 6th-20th week of age. Four isocaloric grower diets containing 8, 10, 12 and 14% CP were randomly allotted to each treatment group. Semen was collected at 25th, 30th, 35th, 45th and 50th week to measure semen volume, sperm concentration, sperm motility and sperm livability. The body weight of different supplemented group differed significantly (p<0.05). The semen volume of 8 and 10% CP diet groups at 25th and 30th weeks were lower than 0.50 ml and the values were significantly different than that of 12 and 14% CP diet groups. But by 35th week there were no significant difference between different CP % groups. The sperm concentration of 8% CP diet group was lower than the other treatment groups. The sperm individual motility of all the treatment groups at different weeks had no significant difference between them. The sperm livability of all the different treatment groups was not significantly different at any week.